Development of a Nonwoven Hemostatic Dressing Based on Unbleached Cotton: A De Novo Design Approach - J. Vincent Edwards; Elena Graves; Nicolette Prevost; Brian Condon; Dorne Yager; Joseph Dacorta; Alvin Bopp (MDPI AG, 2020)
Minimally processed greige (unbleached) cotton fibers demonstrate enhanced clotting relative to highly processed United States Pharmacopeia (USP) type 7 bleached cotton gauze. This effect is thought to be due to the material surface polarity. We hypothesized that a textile could be constructed, conserving the hemostasis-accelerating properties of greige cotton, while maintaining structural integrity and improving absorbance. Spun bond nonwovens of varying surface polarity were designed and prepared based on ratios of greige cotton/bleached cotton/polypropylene fibers. A thromboelastographic analysis was performed on fibrous samples in citrated blood to evaluate the rate of fibrin and clot formation. Lee White clotting times were obtained to assess the material's clotting activity in platelet fresh blood. An electrokinetic analysis of samples was performed to analyze for material surface polarity. Hemostatic properties varied with composition ratios, fiber density, and fabric fenestration. The determinations of the surface polarity of cotton fabrics with electrokinetic analysis uncovered a range of surface polarities implicated in fabric-initiated clotting; a three-point design approach was employed with the combined use of thromboelastography, thrombin velocity index, Lee White clotting, and absorption capacity determinations applied to fabric structure versus function analysis. The resulting analysis demonstrates that greige cotton may be utilized, along with hydrophilic and hydrophobic fibers, to improve the initiation of fibrin formation and a decrease in clotting time in hemostatic dressings suitable to be commercially developed. Hydroentanglement is an efficient and effective process for imparting structural integrity to cotton-based textiles, while conserving hemostatic function.